A guide to implementing criteria based assessment in undergraduate mathematics : mathsassess. (Office for Learning and Teaching, 2014)
Guide to implementing criteria-based assessment in undergraduate mathematics, produced as part of a project that engaged the mathematics community in a conversation around assessment standards which builds upon the Learning and Teaching Academic Standards project outcomes for science, and their contextualisation within the mathematics discipline. The authors aimed to influence assessment practices in mathematics departments, to move away from idiosyncratic marking and grading approaches that favour procedural mastery towards practices that measure the quality of all aspects of student work against external anchors ensuring comparability of standards within and across mathematics departments.